Dolly Parton's Coat of many colors [videorecording (DVD)] - Lind, Alyvia Alyn; Nettles, Jennifer; Schroder, Rick, 1970-; McRaney, Gerald; Parton, Dolly (Warner Home Video, 2016)
A dramatization of one of Dolly Parton's most beloved compositions.